Global data set of long-term summertime vertical temperature profiles in 153 lakes - Pilla Rachel M.; Mette Elizabeth M.; Williamson Craig E.; Adamovich Boris V.; Adrian Rita; Anneville Orlane; Balseiro Esteban; Ban Syuhei; Chandra Sudeep; Colom-Montero William; Devlin Shawn P.; Dix Margaret A.; et al. (NATURE PORTFOLIO, 2025)
Climate change and other anthropogenic stressors have led to long-term changes in the thermal structure, including surface temperatures, deepwater temperatures, and vertical thermal gradients, in many lakes around the world. Though many studies highlight warming of surface water temperatures in lakes worldwide, less is known about long-term trends in full vertical thermal structure and deepwater temperatures, which have been changing less consistently in both direction and magnitude. Here, we present a globally-expansive data set of summertime in-situ vertical temperature profiles from 153 lakes, with one time series beginning as early as 1894. We also compiled lake geographic, morphometric, and water quality variables that can influence vertical thermal structure through a variety of potential mechanisms in these lakes. These long-term time series of vertical temperature profiles and corresponding lake characteristics serve as valuable data to help understand changes and drivers of lake thermal structure in a time of rapid global and ecological change.